Pendekatan Business Model Canvas (BMC) Dan SWOT Analysis untuk Menciptakan Competitive Advantage Di Greenwood Coffee Shop Bojonegoro - Agustino, Muhammad Rizqi; Kustaji, Kustaji; Pratama, Reza Angga; Noor, Fauzian; Irnawati, Dwi (Universitas Respati Indonesia, 2025)
years, driven by increasing domestic coffee consumption and changes in lifestyle, with coffee shops becoming important social spaces. Greenwood Coffee Shop, operating in Bojonegoro, faces the challenge of maintaining its relevance and competitiveness amidst the fierce local market competition. This study aims to identify the factors influencing the competitiveness of Greenwood Coffee Shop by using the Business Model Canvas (BMC) approach and SWOT analysis. The research uses a qualitative approach with a case study on Greenwood Coffee Shop, where data were collected through interviews with the owner, employees, and customers, as well as document analysis and field observations. The results show that Greenwood Coffee Shop has the potential to enhance its competitive advantage through product innovation, leveraging digital media for marketing, and improving service quality. However, the company has not fully utilized a structured business model and SWOT approach in formulating competitive strategies. Therefore, it is recommended that Greenwood Coffee Shop implement a more structured strategy in managing its business to maintain its competitiveness and relevance in the local market